Задача механики разрушения для биматериала с круговой межфазной трещиной под воздействием волны растяжения-сжатия - Меньшиков, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The paper is devoted to the solution of a fracture mechanics problem for a penny-shaped crack located in the interface of two dissimilar media under the action of a tension-compression wave propagating normally to the interface. The stress intensity factors (the opening mode and the transverse shear mode) are obtained in terms of the strain and displacements fields, which are numerically calculated for the vicinity of the crack front.